2018
DOI: 10.3390/w10020120
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Climate Change on Streamflow Hydrology in Headwater Catchments of the Upper Blue Nile Basin, Ethiopia

Abstract: This study assessed the impact of climate change on water availability and variability in two subbasins in the upper Blue Nile basin of Ethiopia. Downscaled future climate data from HadCM3 of A2 (medium-high) and B2 (medium-low) emission scenarios were compared to the observed climate data for a baseline period . The emission scenario representing the baseline period was used to predict future climate and as input to a hydrologic model to estimate the impact of future climate on the streamflow at three future … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(48 citation statements)
references
References 55 publications
6
41
1
Order By: Relevance
“…These changes imply negative consequences for agriculture and water resource availability. The findings are inconsistent with previous studies where warming and wetting were reported for the upper Blue Nile basin Worqlul et al 2018). The discrepancies, particularly in rainfall simulation results, are due to the differences in the spatial and timescales of the studies, types of the model used and climate scenario considered.…”
Section: Spatiotemporal Climate Trendscontrasting
confidence: 99%
“…These changes imply negative consequences for agriculture and water resource availability. The findings are inconsistent with previous studies where warming and wetting were reported for the upper Blue Nile basin Worqlul et al 2018). The discrepancies, particularly in rainfall simulation results, are due to the differences in the spatial and timescales of the studies, types of the model used and climate scenario considered.…”
Section: Spatiotemporal Climate Trendscontrasting
confidence: 99%
“…The simulated mean annual rainfall under RCP4.5 and RCP8.5 is larger than the baseline period. The result showed that the RCP4.5 rainfall simulation increased rates were greater in spring than other seasons, which is in agreement with Worqlul et al (2018) findings in the Upper Blue Nile basin.…”
Section: Discussionsupporting
confidence: 89%
“…The increase in streamflow due to rainfall increment was also discussed by Pandey et al (2017); they revealed that a 28% increase in annual rainfall may result in streamflow increased by approximately 49% from their study in the Armur watershed in Godavari river basin, India. The decrease in streamflow during the rainy season associated with the rainfall reduction corresponds with the findings of Worqlul et al (2018) in the Upper Blue Nile Basin, Ethiopia.…”
Section: Discussionsupporting
confidence: 82%
“…Beles River originates from the escarpment of south-western of Lake Tana, flows towards southwest, and joins the Blue Nile River just before it crosses the Ethio-Sudanese border ( Figure 1). The nature of rainfall in the study area is unimodal and~70-80% of the total rainfall is received between June and September [44], with annual yearly rainfall totals of about 1490 mm. The highly varied topography of the Beles Basin (577 m to 2735 m), together with the highly variable rainfall and temperature, results in contrasting climatic zones within the basin [45].…”
Section: Study Areamentioning
confidence: 99%